Hop Tannins as Multifunctional Tyrosinase Inhibitor: Structure Characterization, Inhibition Activity, and Mechanism - Jiaman Liu; Yanbiao Chen; Xinxin Zhang; Jie Zheng; Weiying Hu; Bo Teng (MDPI AG, 2022)
The application of hops could be extended to obtain higher commercial values. Tannins from hops were assessed for their tyrosinase inhibition ability, and the associated mechanisms were explored. Nuclear magnetic resonance (NMR) and high-performance liquid chromatography-electrospray ionization-tandem mass spectrometry (HPLC-ESI-MS/MS) revealed that the hop tannins were characterized as condensed tannins with (epi)catechin and (epi)gallocatechin as subunits and an average polymerization degree of 10.32. Tyrosinase inhibition assay indicated that hop tannins had an IC50 = 76.52 ± 6.56 μM. Kinetic studies of the inhibition processes indicated the tannins provided inhibition through competitive-uncompetitive mixed reactions. In silico molecule docking showed that tannins were bound to the active site of tyrosinase via hydrogen and electrovalent bonds. Circular dichroism (CD) observed the structural variation in the tyrosinase after reacting with the tannins. Fluorescence quenching analysis and free radical scavenging assays indicated that the tannins had copper ion chelating and antioxidant activities, which may also contribute to inhibition. The intracellular inhibition assay revealed that the melanin was reduced by 34.50% in B16F10 cells. These results indicate that these tannins can be applied as whitening agents in the cosmetics industry.